2013
DOI: 10.1021/sc400472z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Characterization of Hollow Hexagonal NiCo2S4Nanoplates as Pseudocapacitor Materials

Abstract: In this study, the binary transition metal sulfide NiCo 2 S 4 with a novel hollow hexagonal nanoplate (HHNs) structure has been synthesized through a sacrificial template method based on the Kirkendall effect. The hollow nanoplates have an average diameter of about 200 nm, thickness of about 50 nm, and shell thickness of about 10 nm. The resulting samples were characterized by means of XRD, XPS, EDX, SEM, TEM, and HRTEM. The electrochemical characterization results demonstrate that NiCo 2 S 4 hollow hexagonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
178
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(200 citation statements)
references
References 49 publications
19
178
3
Order By: Relevance
“…Figure 1 d,e show the enlarged SEM image of the NiCo 2 S 4 nanosheets on NCF. Overall, the morphologies are conserved after the sulfi dation processes, but the NiCo 2 S 4 nanosheets become thick and rough, which can be further confi rmed through TEM analysis, as shown in Figure 1 f. The NiCo 2 S 4 nanosheets composed of nanoparticles subunits exhibit foldaway silk-like morphology, which can be further confi rmed by TEM image in Figure S3a [ 21,24,28 ] The NiCo 2 S 4 NS grown on NCF can be directly used as binder-free working electrode, which were investigated by cyclic voltammetry (CV), galvanostatic charge/discharge in a three-electrode system. Figure 3 a shows the CV curves of the NiCo 2 S 4 NS/NCF electrode at various scan rates ranged from 5 to 60 mV s −1 .…”
Section: Resultsmentioning
confidence: 73%
“…Figure 1 d,e show the enlarged SEM image of the NiCo 2 S 4 nanosheets on NCF. Overall, the morphologies are conserved after the sulfi dation processes, but the NiCo 2 S 4 nanosheets become thick and rough, which can be further confi rmed through TEM analysis, as shown in Figure 1 f. The NiCo 2 S 4 nanosheets composed of nanoparticles subunits exhibit foldaway silk-like morphology, which can be further confi rmed by TEM image in Figure S3a [ 21,24,28 ] The NiCo 2 S 4 NS grown on NCF can be directly used as binder-free working electrode, which were investigated by cyclic voltammetry (CV), galvanostatic charge/discharge in a three-electrode system. Figure 3 a shows the CV curves of the NiCo 2 S 4 NS/NCF electrode at various scan rates ranged from 5 to 60 mV s −1 .…”
Section: Resultsmentioning
confidence: 73%
“…In the search for high energy density and high power density energy storage devices, electrochemical technologies demonstrate the aptitude to provide the means for electrical energy storage. Amongst the various electrochemical energy storage devices, supercapacitors have drawn much interest due to their extremely high power density, good cycling stability and fast charge-discharge rate compared to conventional capacitors and lithium-ion batteries which possess a low power density and a short cycle life [4][5][6]. However, the relatively low energy density of supercapacitors has not yet met the requirements of electrical systems, ranging from portable electronics to hybrid electric vehicles [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our performance is superior to that of all reported ternary nickel cobalt sulfides based materials (literature reports were summarized in Supplementary Table S1). 24,34,38,40,[46][47][48][49][50] This phenomenon may be attributed to the unique double shell structure which offers many desirable features. First of all, the highly porous double shells surfaces are covered with self-assembled nanosheets which are full of mesopores (with size distribution centered around 3-5 nm, Supplemental Figure S7B).…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26] In addition, it has been well demonstrated that an outer protection layer is important to stabilize the nanostructured ultrathin hollow spheres. [27][28][29] In this sense, double-shell hollow structures of NiCo 2 O 4 with protection outer layer, large surface area, highly porous structure and desirable ionic permeability may be an excellent potential pseudocapacitive material.…”
Section: Introductionmentioning
confidence: 99%